Rethinking the Future of the University - Jeffrey Lyle, David (Mentor Series, 1998)
This distinguished collection of essays, edited under the direction of David Lyle Jeffrey and Dominic Manganiello, emerged from the discussions that surrounded the 1995-1996 McMartin Lectures. Dedicated to studying the relationship and contributions of historic Christian thought to the intellectual life of university disciplines, this series of lectures served as an occasion for scholars to rethink the present crisis in the relationship between the historic identity of the university and the development of the modern university.